Tinjauan Yuridis terhadap Perkawinan Beda Agama di Indonesia dalam Perspektif Undang-Undang Perkawinan dan Hak Asasi Manusia - Sindy Cantonia; Ilyas Abdul Majid (CV Rewang Rencang, 2021)
As a plural country, Indonesia has a diversity of religions and beliefs so that it can indirectly potentially encourage the practice of interfaith marriage. The Marriage Act does not explicitly regulate interfaith marriage, resulting in two interpretations: First, interfaith marriage is prohibited because it does not meet the legal requirements of marriage; and Second, interfaith marriage is permissible because there is no provision governing it. The right to marry and have a family is a guaranteed human rights in international human rights instruments and Indonesian laws and regulations. Thus the difficulty of the implementation of interfaith marriage and the absence of legal provisions governing it can lead to violations of human rights.